The effect of a new teaching methodology on learning performances of automotive - mechatronics students - KÜÇÜK, HALUK; ERSOY, SEZGİN (ELSEVIER SCIENCE BV, 2010)
In this study a new methodology for teaching of Automotive Mechatronics course is proposed. The students who have taken the course were divided into two groups: the first, for classical mode of teaching and the other for the new model of instruction. The performance of the students were measured by pre-test and post-test. The results show that, handing out the class material beforehand and having the students learn by practicing in the laboratory, increase the students' interest and success when compared to those being taught the theory, in class and having completed the experiments in the lab afterwards. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Automotive; mechatronics; education; method; EDUCATION; INDUSTRY